2002
DOI: 10.1093/hmg/11.12.1373
|View full text |Cite
|
Sign up to set email alerts
|

Association and linkage analyses of RGS4 polymorphisms in schizophrenia

Abstract: Gene expression analyses of postmortem cerebral cortex suggest that transcription of the regulator of G-protein signaling 4 (RGS4) is decreased in a diagnosis-specific manner in subjects with schizophrenia. To evaluate the possible role of RGS4 in the pathogenesis of schizophrenia, we conducted genetic association and linkage studies using samples ascertained independently in Pittsburgh and New Delhi and by the NIMH Collaborative Genetics Initiative. Using the transmission disequilibrium test, significant tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
155
2
3

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(170 citation statements)
references
References 35 publications
10
155
2
3
Order By: Relevance
“…SNP 90387 A/A was found to be marginally significantly associated with schizophrenia in individual homozygous for either the efficient or inefficient 3-SNP COMT haplotype, which is consistent with findings reported for 90387 in both the Pittsburgh Schizophrenia and NIMH family samples (Chowdari et al 2002); however, Chowdari et al (2002) also reported haplotypes carrying the G allele were significantly associated with schizophrenia in the NIMH family sample. It is unclear why the 90387 A/A genotype increases risk for both the efficient and inefficient 3-SNP COMT haplotype homozygote groups.…”
Section: Rgs4supporting
confidence: 84%
See 2 more Smart Citations
“…SNP 90387 A/A was found to be marginally significantly associated with schizophrenia in individual homozygous for either the efficient or inefficient 3-SNP COMT haplotype, which is consistent with findings reported for 90387 in both the Pittsburgh Schizophrenia and NIMH family samples (Chowdari et al 2002); however, Chowdari et al (2002) also reported haplotypes carrying the G allele were significantly associated with schizophrenia in the NIMH family sample. It is unclear why the 90387 A/A genotype increases risk for both the efficient and inefficient 3-SNP COMT haplotype homozygote groups.…”
Section: Rgs4supporting
confidence: 84%
“…At both SNP4 and SNP18 the G/G genotype was found to increase risk of schizophrenia approximately 2.5 to 4-fold, which is in agreement with Chowdari et al (2002), , Morris et al (2004) and Williams et al (2004) for SNP4 and with Chowdari et al (2002), , Morris et al (2004), Corderiro et al (2005 and for SNP18. Although the opposite allele was found to be positively associated in three studies for SNP4 (Chowdari et al 2002;Williams et al 2004;Cordeiro et al 2005), the majority of the studies for SNP18, including ours, are in agreement that the G allele confers risk for schizophrenia, although at least one study did not find association between SNPs 1, 4, 7, and 18 and schizophrenia (Sobell et al 2005). Moderately strong LD exists between these SNPs, so these results cannot be considered completely independent.…”
Section: Rgs4supporting
confidence: 70%
See 1 more Smart Citation
“…In recent years, a number of genetic polymorphisms have been identified that impact cognition and risk for neuropsychiatric illness. Genes that have been implicated in schizophrenia include catechol-O-methyl transferase (COMT: Li et al 1996;Kunugi et al 1997;Li et al 1999;Egan et al 2001;Shifman et al 2002;Chen et al 2004), neuregulin I (NRG1: Stefansson et al 2002Stefansson et al , 2003Yang et al 2003;Tang et al 2004;Corvin et al 2004), regulator of G-protein signaling 4 (RGS4: Mirnics et al 2001;Chowdari et al 2002, Williams et al 2004; Morris et al 2004), dysbindin (DTNBP1: Straub et al 2002;Schwab et al 2003;Numakawa et al 2004), G72 (Chumakov et al 2002;Korostishevsky et al 2004;Schumacher et al 2004;Korostishevsky et al 2005;Zou et al 2005), disrupted-inschizophrenia 1 (DISC1: St Clair et al 1990;Hennah et al 2003;Callicott et al 2005;Millar et al 2005), and metabotropic glutamate receptor-3 (GRM3: Marti et al 2002;Fujii et al 2003;Egan et al 2004;Chen et al 2005). A number of other genes are also under active investigation, and the total number of potential susceptibility genes continues to rise (Harrison and Weinberger 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The cases of RGS4 and PDLIM5 provide examples to illustrate the value of combining genome-wide transcriptome studies with mutation analysis. Expression of RGS4 mRNA was specifically down-regulated in postmortem cortex of patients with schizophrenia and not in patients with major depressive disorder (Mirnics et al 2001) and four SNPs (Single Nucleotide Polymorphisms) were associated, three of them were located at~7 kb from the 5¢UTR end and another in the first intron of the gene (Chowdari et al 2002;Chen et al 2004;Morris et al 2004;Williams et al 2004). RGS4 (Regulator of G-protein Signalling 4) is a GTPase-activating protein that inhibits the action of metabotropic receptors, including glutamate receptors (De Blasi et al 2001).…”
Section: Combining Genetics and Global Transcriptome Studiesmentioning
confidence: 99%